The Influence of the Teaching Games For Understanding Learning Model to Improve Poetry Reading Skills at UPT SDN 37 Pinrang - Hasrijah Hasrijah; Ismail Ismail; Nadar Nadar (Universitas Muhammadiyah Enrekang, 2024)
This research aims to analyze the effect of Teaching Games for Understanding (TGfU) learning model on improving poetry reading skills among fifth-grade students at UPT SDN 37 Pinrang. The study employed a quantitative approach with a quasi-experimental design using pretest-posttest control group design. The research sample consisted of 56 fifth-grade students divided into an experimental group (n=28) taught using the TGfU model and a control group (n=28) taught using conventional methods. Research instruments included poetry reading ability tests, observation sheets, student response questionnaires, and interview guidelines. Data were analyzed using descriptive and inferential statistics. Results showed that: (1) The implementation of the TGfU model in poetry reading instruction was carried out through six stages: Game Form, Game Appreciation, Tactical Awareness, Making Appropriate Decisions, Skill Execution, and Performance; (2) There was a significant effect of the TGfU learning model on improving students' poetry reading ability (t-value=6.283; p<0.05) with the experimental group's average improvement (22.82) higher than the control group (10.18); (3) Students' responses to the TGfU learning model were in the very positive category with an average score of 3.65. The highest improvement occurred in the expression and appreciation aspects, indicating the effectiveness of the TGfU model in developing affective competencies in poetry reading. This research concludes that the adaptation of the TGfU model, which emphasizes games and student activity, effectively improves poetry reading skills.